Semi-I-Expandable Ideal Topological Spaces - Chawalit Boonpok (Journal of Mathematics)
Our purpose is to introduce the notion of semi-I-expandable ideal topological spaces. Some properties of semi-I-locally finite collections are investigated. In particular, several characterizations of semi-I-expandable ideal topological spaces are established.